The role of gut microbiota in patients with autoimmune thyroid diseases – current status and future perspectives - Litwińczuk, Michał; Szydełko, Joanna; Szydełko, Magdalena (Journal of Education, Health and Sport, 2019)
Introduction: Autoimmune diseases constitute a significant clinical problem, due to the increasing incidence, that is why the potential causes that determine their occurrence are sought. Intestinal microbiota greatly outnumber the all of human body’s cells. Its metabolic activity and disorders in the structure, resulting from, for example, antibiotic therapy, lead to homeostasis dysregulation, and in this way gain a new meaning in the etiology of autoimmune diseases.Aim of the study: This article summarizes the current knowledge about gut microbiota in patients with autoimmune thyroid diseases as well as discussed the alterations in the gut microbiota and their potential relationship with thyroid cancer.Description of knowledge: The analyzed scientific literature revealed a relationship between the occurrence of autoimmune diseases and intestinal flora disorders. It is believed that the microbiota that colonized the entire human body, due to diversity, co-formation of the intestinal barrier, its own metabolic activity and participation in many metabolic processes, plays an important role in regulating the immune system functioning. Many data indicate, that the changes in the composition of the intestinal flora in many autoimmune diseases can also be influenced by individual factors, environmental conditions, genetic predisposition, and diet. Conclusions: Gut microbiota is an important element of the immune system and due to the demonstrated changes in its composition in various disease processes and its significant effects on metabolism, the researchers are still underway to clarify all pathogenetic mechanisms of microbiota influencing human homeostasis. Therefore, further studies are required to determine the effect of microbiota and its role in the pathogenesis of autoimmune diseases.